Analysis of the Influence of Drilling Parameters and Monitoring of the Delamination Phenomenon in Thermoplastic CFRP Machining - Kondo, Marcel Yuzo [UNESP]; Callisaya, Emanuele Schneider [UNESP]; Botelho, Edson Cocchieri [UNESP]; Costa, Michelli Leali [UNESP]; de Sampaio Alves, Manoel Cléber [UNESP]; Ribeiro, Marcos Valério [UNESP] (My University, 2023)
Carbon fiber reinforced Polyamide 6 (Nylon 6) composites have a high potential for use in the aerospace, automotive, and energy industries. Parts of polymeric composites are generally manufactured in dimensions close to those used by the hot compression molding process. However, the assembly of these components in manufacturing a product occurs by riveting or screwing, which makes it necessary to drill holes. The central hole quality problem during the machining of carbon fiber-reinforced polymeric composites (CFRP) is the delamination phenomenon. Separating the composite layers at the entrance of the cutting tool (peel-up delamination) and exit (push-out delamination) harms the resistance, stiffness, and reliability of the components. Many strategies are used to suppress the occurrence of delamination, including the selection of suitable machining parameters, the use of specific tool geometries, and the use of different materials for making drills. Ways of monitoring the drilling process to prevent delamination are also researched. The present study aimed to analyze the drilling process of a thermoplastic polymeric composite reinforced with carbon fibers, verifying the influence of the variation in the drilling parameters of cutting speed and feed rate in the thrust force and push-out delamination factor. It was carried out through two different 32 full factorial matrices, testing cutting speed from 35.95 to 133.12 m/min and feed rate from 0.018 to 0.118 mm/rev. It also investigated the potential use of thrust force signals for monitoring delamination formation during the drilling process.